The effect of personal capital and loan capital upon net revenue at KSPPS BMT Binaul Ummah Bogor City - Endang Silaningsih; Vivih Rahmayanti (STIE Binaniaga, 2019)
The purpose of the research is to analyze: 1) personal capital, loan capital, and net revenue at the KSPPS BMT Binaul Ummah; 2) the effect of personal capital and loan capital simultaneously upon net revenue at KSPPS BMT Binaul Ummah; 3) the effect of personal capital and loan capital partially upon net income at KSPPS BMT Binaul Ummah. The design of the quantitative research has used descriptive method and verification one and secondary data. Subject of this research is KSPPS BMT Binaul Ummah Bogor City and the object of this research is the annual report of KSPPS BMT Binaul Ummah from 2013-2017 regarding net revenue, personal capital and loan capital. The analysis tool uses multiple regression F test and t test with a probability level of five percent. The results of the research show that the description of personal capital, loan capital and net revenue in general is fluctuating annually. Net revenue has significantly decreased every year. Simultaneously personal capital and loan capital have a positive and significant effect upon net revenue at the Cooperative Business Unit of KSPPS BMT Binaul Ummah. Partially personal capital does not have a positive and significant effect upon net revenue of the co-operative business unit. However, loan capital has a positive and significant effect upon net revenue at KSPPS BMT Binaul Ummah. Keywords: Personal Capital, Loan Capital, Net Revenue, Co-operative business unit